Pengaruh Pengawasan Legislatif dan Temuan Audit terhadap Internet Financial Report Pemda Dimoderasi Sistem Pengendalian Internal - Indirasani, Dianisa; Akram, Akram; Santoso, Budi (E-Jurnal Akuntansi; Vol 31 No 12 (2021), 2021)
This study aims to provide empirical evidence regarding the effect of legislative oversight and audit findings on the disclosure of Internet Financial Reports (IFR) for the local governments of NTB, NTT and Bali (Bali Nusra), as well as the moderating effect of the internal control system (SPI). The total population of the study was 44 local governments consisting of provincial, district and city governments in Bali Nusra. The study was conducted during 2018-2019 with a total of 88 observations. The sampling method used non-probability sampling with saturated sampling (census). The results of the study indicate that legislative oversight has a positive and significant impact on the disclosure of the Bali Nusra Regional Government's IFR. Meanwhile, the audit findings have no significant negative effect on the disclosure of the Bali Nusra Regional Government IFR. In addition, the SPI strengthens but is not significant in moderating the effect of legislative oversight and audit findings on the disclosure of IFR for the local government of Bali Nusra. The implication of this research is to provide input to the heads of local governments as consideration for improving the implementation of IFR, as a benchmark and form of evaluation related to the implementation of IFR to increase transparency. Keywords : Legislative Oversight; Audit Findings; Internal Control System; Internet Financial Report.